2013
DOI: 10.1016/j.socscimed.2012.11.022
|View full text |Cite
|
Sign up to set email alerts
|

To what extent do biomarkers account for the large social disparities in health in Moscow?

Abstract: The Russian population continues to face political and economic challenges, has experienced poor general health and high mortality for decades, and has exhibited widening health disparities. The physiological factors underlying links between health and socioeconomic position in the Russian population are therefore an important topic to investigate. We used data from a population-based survey of Moscow residents aged 55 and older (n=1495), fielded between December 2006 and June 2009, to address two questions. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…For example, in the analysis of 1189 initially high functioning men and women aged 70–79 years from the MacArthur study of Successful Aging, Seeman et al 14 have demonstrated that approximately one-third of the educational differences in mortality was mediated by the summary index of AL. Another study found that biological risk accounted for a substantial portion (between 19% and 36%) of social disparities in health among participants of the Survey on Stress, Aging, and Health in Russia 15. A Taiwanese study showed that higher AL was independent determinant of self-rated health but no explanatory factor for socioeconomic differentials in health 33.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the analysis of 1189 initially high functioning men and women aged 70–79 years from the MacArthur study of Successful Aging, Seeman et al 14 have demonstrated that approximately one-third of the educational differences in mortality was mediated by the summary index of AL. Another study found that biological risk accounted for a substantial portion (between 19% and 36%) of social disparities in health among participants of the Survey on Stress, Aging, and Health in Russia 15. A Taiwanese study showed that higher AL was independent determinant of self-rated health but no explanatory factor for socioeconomic differentials in health 33.…”
Section: Discussionmentioning
confidence: 99%
“…Using data from the MacArthur study, Seeman et al have identified that lower SEP is associated with increased AL, and that AL mediates the relationship between SEP and mortality, explaining around 35% of the difference in mortality attributable to educational differences 14. Similarly, another study found that biological risk factors explained 19% of the educational differences in general health 15. In contrast to these findings, an analysis based on the Taiwanese social environment and biomarkers of ageing study failed to find support for the mediating role of AL biomarkers in explaining the social gradient in health 12.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the results for males showing underestimation of CVD mortality risk using conventional SCORE-High and recalibrated SCORE-MoSP equations can be explained by specific CVD risk factors in Russia [2731]. The findings also warn that conventional SCORE-High equations cannot adequately predict the elevated CVD mortality risk in Russia even if national or sub-national mortality data are used.…”
Section: Discussionmentioning
confidence: 99%
“…The Russian LRC studies found that differently from other developed countries showing increasing CHD risk with increasing levels of cholesterol, this relationship among adult males in Russia was non-linear but rather U or J shape [21]. Finally, there is some evidence that psychosocial factors such as stress, effort-reward imbalance, and a lack of social support, which were unaccounted for in the original and recalibrated SCORE algorithms, may also explain a substantial part of elevated risk of cardiovascular diseases in Russia [30, 31]. …”
Section: Discussionmentioning
confidence: 99%
“…Anthropometry included body height measured with a wall-mounted stadiometer, body weight measured with calibrated scales, waist and hip circumferences measured with a calibrated tape in the standing position [43]. The standard cutoffs were used to define low versus high-risk levels of total cholesterol, high density lipoproteins (HDL), triglycerides [48], obesity [49], waist circumference [50], Glycosylated hemoglobin (Hb) [51] and C-reactive protein (CRP) [52] that had been previously used with the SAHR data ( Table 1) [53]. For a few other biomarkers, the high-risk group was defined as the highest quintile of unweighted sex-specific distribution for interleukin-6 (IL-6) and fibrinogen vs. all others (Table 1).…”
Section: Health Outcomes and Biological Markers Of Healthmentioning
confidence: 99%